(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Rola odpowiednio uregulowanego wynagrodzenia sędziowskiego dla prawidłowego funkcjonowania wymiaru sprawiedliwości oraz zagwarantowania zasady niezawisłości sędziowskiej jest nie do przecenienia. Artykuł niniejszy ma na celu przedstawienie pogłębionych rozważań na temat statusu materialnego sędziów sądów powszechnych w Polsce, zarówno w ujęciu teoretycznym, porównawczym jale i w opiniach i oczekiwaniach samych sędziów. Opinie sędziów; przywoływane w niniejszym artykule, uzyskane zostały w drodze badań ankietowych, przeprowadzonych przez autora artykułu w czerwcu i lipcu 2007 roku. Wzięło w nichudział 687 sędziów sądów powszechnych wszystkich szczebli (wraz z asesorami sądowymi sądów rejonowych) z terenu całej Polski; wybranych losowo według kryterium losowania sądów (sędziowie, którzy wzięli udział w badaniu stanowią 54,7% wszystkich zaproszonych do wzięcia udziału w badaniu). Opinie te nie odzwierciedlają oczekiwań sędziów Sądu Najwyższego, Trybunału Konstytucyjnego oraz sądów wojskowych i administracyjnych, bowiem badanie przewidywało uzyskanie odpowiedzi od najliczniejszej jak też najbardziej reprezentatywnej grupy sędziów w ramach jednolitej struktury organizacyjnej. A proper and adequate judicial remuneration is one of the basic safeguards of an independent and strong judiciary. The article aims to present an endeepe ned view on Polish judicial remunerations, and includes an analysis of law, juri sprudence, social reality and opinions of judges themselves. The basis for the ana lysis of judicial expectations in relations to remunerations, was a wide-range su rvey among 687 judges of Polish common courts (i.e. regional, circuit and appeal courts), conducted on June 2007. Poland as one of post-communist countries after 20 years of transformation, is continuously developing its democratic insti tutions and improving safeguards of the rule of law. Although the way towards the western democracies is already impressive and in many ways successful, a number of important issues have not been solved in a satisfactory way: One of them is the position of Polish judges among other state powers and the econo mical position of judges in comparison with judges of other EU Member States. This raises serious concerns and calls for changes. According to research conduc ted by the Council of Europe in 2006, Polish judges are almost at the very end of European statistics, when it comes to comparison of their salaries. That causes serious implications to proper conduct of their duties, as well as to their indepen dence and the whole rule of law. A survey conducted among judges, and presented in this article, proves that the level of dissatisfaction raises a number of problems (e.g. strong willingness of migration to better paid legal professions). Moreover it indicates dangerous points in the legal system (e.g. unjust disproportions in re munerations, lack of balance between the executive and judicial power) that re quire immediate change. The article is a comprehensive and analytic insight in the finances-related problems of Polish judiciary.